2017
DOI: 10.1016/j.bpj.2017.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Compartmental and Spatial Rule-Based Modeling with Virtual Cell

Abstract: In rule-based modeling, molecular interactions are systematically specified in the form of reaction rules that serve as generators of reactions. This provides a way to account for all the potential molecular complexes and interactions among multivalent or multistate molecules. Recently, we introduced rule-based modeling into the Virtual Cell (VCell) modeling framework, permitting graphical specification of rules and merger of networks generated automatically (using the BioNetGen modeling engine) with hand-spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 23 publications
0
46
0
Order By: Relevance
“…Biophysical models of these systems may serve to address the interplay of valency and geometry by systematically varying the cellular and molecular features underlying these properties. Stochastic reactiondiffusion modeling at the cellular scale cannot fully account for steric effects or molecular flexibility because molecules are typically modeled as infinitesimal points in space (17)(18)(19). In principle, multimolecular/multistate interactions could be modeled with atomistic molecular dynamics simulations, but the large sizes of these systems and the need to simulate on the second timescale make such simulations computationally impractical.…”
Section: Introductionmentioning
confidence: 99%
“…Biophysical models of these systems may serve to address the interplay of valency and geometry by systematically varying the cellular and molecular features underlying these properties. Stochastic reactiondiffusion modeling at the cellular scale cannot fully account for steric effects or molecular flexibility because molecules are typically modeled as infinitesimal points in space (17)(18)(19). In principle, multimolecular/multistate interactions could be modeled with atomistic molecular dynamics simulations, but the large sizes of these systems and the need to simulate on the second timescale make such simulations computationally impractical.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also demonstrated that alternative drug scheduling regimens may have benefits compared to traditional single-agent applications or up-front combinations 45,126 . Our work suggests extending these approaches to account for all levels of heterogeneity in tumors, i.e., genetic profiling to enumerate dominant genetic states, followed by characterization of the associated epigenetic landscapes using single-cell experimental approaches, possibly aided by advanced theoretical and computational modeling techniques 41,64,65,73,[127][128][129][130][131][132] . These landscapes can then be screened against batteries of available drugs, in vitro and in silico, to devise individualized treatments that can be tested against patient-derived xenografts in vivo before being administered clinically.…”
Section: Discussionmentioning
confidence: 99%
“…A number of analysis packages that make use of PC data have been developed (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52) . Here we briefly describe several tools developed by the PC team.…”
Section: Analytical Tools Using the Pathway Commons Data Sourcementioning
confidence: 99%